Perancangan Sistem Kontrol Suhu Dan Kelembaban Pada Ruangan Budidaya Jamur Tiram Berbasis IoT - Nuzulul Septiana Devi; Danang Erwanto; Yudo Bismo Utomo (Universitas Muhammadiyah Ponorogo, 2018)
Oyster mushrooms besides good also have many benefits for health but in its cultivation requires a fairly complicated treatment. Mushroom farmers have difficulty in regulating temperature and humidity in real time. If the temperature and humidity of the environment where the mushrooms grow is not as needed, it will inhibit the growth of fungi. To overcome this problem, it is proposed to make an Internet of Things based temperature and humidity control device. In this study the main components used are the Dht11 sensor and Arduino Uno and connected via Android via the Esp826601 module. The temperature and humidity suitable for oyster mushrooms are not 25oC and not 75%. The temperature and air humidity are detected by the Dht11 sensor and the measurement results from Dht11 are displayed on Lcd then the temperature and humidity values are sent to the android user via the Esp8266-01 module. The function of this android is besides being used to display the value of temperature and humidity also functions as a remote controller, there are 2 buttons to turn on / off the Dc Fan and the Water Faucet. Dc fan serves to increase the humidity of the air if the humidity is less according to the needs of the fungus and the water faucet serves to reduce the temperature if the temperature in the kumbung is too hot. The use of the internet of things concept aims to facilitate the work of mushroom farmers because farmers can monitor temperature and humidity and take action through their androids even though farmers are far from the mushroom cultivation site as long as the device is connected to the internet network